UTILIZATION OF JAPANESE LANGUAGE TEXTBOOKS TO IMPROVE STUDENT RESULTS CASE STUDY AT SMAN 33 WEST JAKARTA - Rosidah - (International Journal of Education, Information Technology, and Others, 2018)
In general, this study aims to describe the use of textbooks for class X Japanese language lessons at SMAN 33 West Jakarta. In particular, this study aims to find out more deeply about the use of Japanese textbooks and student learning outcomes. This research was conducted at SMAN 33 West Jakarta. This research was conducted in March 2018 until November 2018. The research method used qualitative methods (seeing social phenomena through case studies / case studies) with primary data and secondary data. Research Results Shows that Japanese textbooks Nihongo Kirakira and Sakura have been used well in Japanese subjects at SMAN 33 West Jakarta. Utilization is carried out intensely both during class and outside lessons independently by students with various forms of activities such as being a source of learning, doing assignments, gradual training, project presentation and reflection of learning material.